Phytotaxa 100: The rise of a major journal in systematic and taxonomic botany - Zhang, Zhi-Qiang; Esser, Hans-Joachim; Christenhusz, Maarten J.m. (Phytotaxa, 2013)
Today, the 23rd of May, is the 305th birthday of Carl Linnaeus—father of plant taxonomy and founder of the modern scheme of binomial nomenclature. To join international celebrations of his birthday, we publish Phytotaxa 100, at the same time marking an important milestone in the history of this journal of botanical taxonomy. It is timely that we review its development in the past, especially against the objectives that we set for Phytotaxa (Christenhusz et al. 2009, 2011a), and to assess its current position among journals of systematic botany.